Analisis Kebijakan Program Peremajaan Sawit Rakyat Melalui Badan Pengelola Dana Perkebunan Kelapa Sawit (BPDPKS) Di Kabupaten Labuhanbatu Selatan. - Siahaan, Jannes Maringan; Siregar, Tumpal H.S.; Siahaan, Elisabeth (Universitas Medan Area, 2020)
his study aims to analyze the policies of the community oil palm rejuvenation program through the oil palm plantation fund management agency (BPDPKS) in South Labuhanbatu Regency. The data analyzed were obtained from the research location in Aek Raso Village, Torgamba Subdistrict, South Labuhanbatu Regency by conducting structured interviews with 165 farmers who applied for aid. This rejuvenation program policy has requirements consisting of administrative aspects and financing aspects. Research shows that the value of aid funds provided by the government in implementing oil palm rejuvenation has not been able to support the costs required. The percentage of farmers who have 2 ha of land area is 78.8% while those who have 4 ha of land area are 21.2%, the age of productive farmers is 68% while 32% of age is not productive. Farmers who have a legality of land as much as 36% and who are not legal as much as 64%. This policy has not been specific to the location proven from the data of 282 farmers who are members of the Gapoktan, there are 16% have not been able to take advantage of the policy. Costs needed by farmers from the beginning of planting until the maintenance period of the 3rd year is Rp. 60,364,349. Through indicative costs set by the government of Rp. 66,437,000, the difference in average value of farmers' needs is less than that set by the government, which is valued at Rp. 6,072,651, or 9.14%. Based on government funding of Rp. 25,000,000, - / ha / farmer then to meet the cost of rejuvenation of oil palm, farmers need matching funds with an average value of Rp35,364,349 / ha / farmer or 59% of the total funds.